A animação no documentário: uma frágil fronteira entre sonho e realidade - Fabio Lucas Belotte (2015)
The line that separates dreams from reality is thin; after all, how much of reality is in a dream, and how much of dream is in reality? The line that separates animation from documentary works the same way. According to the more traditionalist theories, opposing narrative structures help maintain the fantasy behind the animated image, while live action footage offers an irrefutable truth. Nevertheless, the history of cinema reveals that the association between documentary and animated films began in the early 1900s. While the moving image was still taking its first steps, animation technique was valued for its unique characteristic of adhering to different narrative structures. Even during times of technical limitations the animators could employ their innate subjectivity to tell a story based on reality, using the power of images to share knowledge only passed down through oral tradition, to convey political and social messages, and to educate. This research examines the effects animated images have over documentary narratives; it aims to go through the most important issues that instigate the discussion about documentary works as a model for the legitimization of truth, and about animation as the precursor of intangible images that go beyond the representation through the photographic image and the verisimilitude with reality.